Efectos de las noticias sobre violencia en el clima social universitario: estudiantes de comunicación Utmach - González Vega, Camila De Las Mercedes (Machala, 2024)
In this research work, the central premise was to know what the effects of the consumption of red chronicle news are on the social climate within the classrooms of the Communication Career, at the Technical University of Machala. To delimit and promote the specification within what was studied, five news items were collected from the media MP Noticias disseminated through the social network Telegram, in which this digital channel from the province of El Oro, Ecuador, shares information with its audience. The main question to be resolved was: how does the consumption of violent news disseminated on the Telegram platform, specifically on the media channel MP Noticias, affect communication students at UTMACH, individually and collectively? The information collection techniques characterized the present study with a mixed approach methodology, applying three research instruments: bibliographic review, questionnaire questions to interview specialists in the area of ​​psychology and pedagogy; finally, focus group form applied to a sample selected by convenience, from the target group. The main results denoted an iota of resilience in terms of the effect of frequent exposure to news that covers topics of violence and is accompanied by explicit visual elements. Thanks to the documentary research and the responses of the interviewees, it was stated that there is a consequence on the social climate (interpersonal communication, language, perception of security) if students are constantly exposed to visual elements about violence in red chronicle news; However, during the application of the focus group technical sheet, 75% of those interviewed responded that seeing this type of information daily does not alter their behavior, therefore, it does not influence the intraclass social climate.
En el presente trabajo de investigación se tuvo como premisa central conocer cuáles son los efectos del consumo de noticias de crónica roja en el clima social dentro de las aulas de la Carrera de Comunicación, de la Universidad Técnica de Machala. Para delimitar y fomentar la especificación dentro de lo estudiado, se recopilaron cinco noticias del medio MP Noticias difundidas a través de la red social Telegram, en la que este canal digital de la provincia de El Oro, Ecuador, comparte información con su audiencia. La cuestión principal a resolver fue: ¿cómo los estudiantes de comunicación en la UTMACH perciben el consumo de noticias violentas, difundidas específicamente en el canal de MP Noticias en Telegram, en cuanto a sus consecuencias en el clima social interno? Las técnicas de recopilación de información caracterizaron el presente estudio con una metodología de enfoque mixto, aplicando tres instrumentos de investigación: revisión bibliográfica, cuestionario de preguntas para entrevistar a especialistas del área de la psicología y pedagogía; por último, ficha de focus group aplicada a una muestra seleccionada por conveniencia, del grupo objetivo. Los principales resultados denotaron un ápice de resiliencia en cuanto al efecto de la exposición frecuente a noticias que abarcan temas de violencia y son acompañadas de elementos visuales explícitos. Gracias a la investigación documental y las respuestas de los entrevistados, se afirmó que existe una consecuencia en el clima social (comunicación interpersonal, lenguaje, percepción de seguridad) si se expone a los estudiantes constantemente a elementos visuales sobre violencia en noticias de crónica roja; no obstante, durante la aplicación de la ficha técnica del focus group, 75% de los entrevistados respondieron que ver diariamente este tipo de información no altera su comportamiento, por ende, no influye en el clima social intraclase.
Keywords: CLIMA SOCIAL UNIVERSITARIO; CRONICA ROJA; NOTICIAS; EFECTOS; VIOLENCIA.